Analisis Penerapan Standar Akuntansi Keuangan Entitas Miro Kecil Menengah pada Usaha Mikro, Kecil dan Menengah - Adi Putra, Nyoman Arya; Suartana, I Wayan (E-Jurnal Akuntansi, 2023)
This research was conducted with qualitative descriptive data research through a case approach. This study aims to determine the application of SAK EMKM to the Sami Pet Shop business. The object of this research is the financial report of the MSME Sami Pet Shop. The research conducted at the Sami Pet Shop SMEs is a qualitative research with a comparative descriptive approach, data collection techniques using interviews and documentation studies. The results of this study indicate that the Sami Pet Shop created only keeps records of income and costs (expenses) in its business. In Sami Pet Shop's bookkeeping, it can be seen that there is no clear separation between income accounts and expense accounts. The factors that cause Sami Pet Shop's business not to apply SAK EMKM to its financial statements are the lack of knowledge and understanding of Sami Pet Shop owners about accounting standards in preparing financial statements